2023
DOI: 10.1002/jev2.12378
|View full text |Cite
|
Sign up to set email alerts
|

RTP801 mediates transneuronal toxicity in culture via extracellular vesicles

Júlia Solana‐Balaguer,
Núria Martín‐Flores,
Pol Garcia‐Segura
et al.

Abstract: Extracellular vesicles (EVs) play a crucial role in intercellular communication, participating in the paracrine trophic support or in the propagation of toxic molecules, including proteins. RTP801 is a stress‐regulated protein, whose levels are elevated during neurodegeneration and induce neuron death. However, whether RTP801 toxicity is transferred trans‐neuronally via EVs remains unknown. Hence, we overexpressed or silenced RTP801 protein in cultured cortical neurons, isolated their derived EVs (RTP801‐EVs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 196 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…Recent studies showed that neuron-derived EVs can contain toxic proteins that contribute to the progression of neurodegenerative diseases [ 160 ]. Meanwhile, You et al [ 161 ] suggested that ATPase Na + /K + transporting subunit alpha 3 (ATP1A3) isolating from neuron EVs can be a potential diagnostic biomarker of neurodegenerative diseases.…”
Section: Role Of Adipose Tissue-derived Evs In Metabolic Diseasesmentioning
confidence: 99%
“…Recent studies showed that neuron-derived EVs can contain toxic proteins that contribute to the progression of neurodegenerative diseases [ 160 ]. Meanwhile, You et al [ 161 ] suggested that ATPase Na + /K + transporting subunit alpha 3 (ATP1A3) isolating from neuron EVs can be a potential diagnostic biomarker of neurodegenerative diseases.…”
Section: Role Of Adipose Tissue-derived Evs In Metabolic Diseasesmentioning
confidence: 99%